Evaluation of Matrix Metalloproteinases-2 (MMP-2) and Tissue Inhibitors of Metalloproteinases-2 (TIMP-2) in Oral Submucous Fibrosis and Their Correlation With Disease Severity - Shrestha, A; Carnelio, S (Kathmandu University Medical Journal, 2015)
Background Oral submucous fibrosis (OSF), a potentially malignant oral lesion, is a form of pathological fibrosis affecting the oral mucosa. It results from an imbalance in equilibrium of the normal process of synthesis and degradation of extra cellular matrix. Matrix metalloproteinases and its inhibitors play important role in remodeling of the extra cellular matrix which are important in progression and pathogenesis of potentially malignant lesions to malignancy.Objectives To evaluate the expression and distribution of Matrix metalloproteinases-2 (MMP- 2) and Tissue inhibitor of metalloproteinases-2 (TIMP-2) in different grades of Oral Submucous Fibrosis(OSF).Method Immunohistochemical analysis for MMP-2 and its TIMP-2 was performed in 30 histopathologically confirmed, formalin fixed, paraffin embedded specimens of OSF. A semi-quantitative analysis was done to assess the expression, distribution and comparison of these in various stages of this disease.Result All moderately advanced cases and 64.2% for MMP-2 and 78.5% for TIMP-2 of early stage cases showed positivity. Between two stages of OSF, statistically significant differences were noted in expression of TIMP-2 in lamina propria, deep connective tissue and supra basal layers (p